“Neither Am I Afraid of the Black.”The Relationship with the Mother in the Texts of Janina Degutytė - Šmitienė, Giedrė (Literatūra, 2018)
[full article and abstract in Lithuanian; abstract in English] This article is intended to describe the relations of the poetess and translator Janina Degutytė (1928–1990) with her mother. The poetry of Degutytė was exceptionally popular in the 1960s and the 1970s; it was read and rewritten by hand. In 1980, literary critic Viktorija Daujotytė was preparing a monograph about Degutytė and asked the poetess to answer some usual questions in written form. The answers from the poetess revealed her tragic childhood due to an alcohol addicted and aggressive mother. These “answers” were not known to the wide audience until they were published in 1996 as a separate publication, together with an “unfinished autobiography,” written during the last months of poetess’s life. This written story about the author’s childhood was the first and, so far, the only Lithuanian text revealing the dark side of motherhood; thus, it became an important text in Lithuanian culture. This article is an attempt to describe and understand the relationship of the poetess Degutytė with her mother. It is based on letters, autobiographical texts and poems. There are two approaches developed in the article: a phenomenological atnhropological approach, which allows us ask what kind of life was lived and how was it lived, and a narratological approach, which helps us understand how the lived life was told in words. The epistolaric material, because of its sheer quantity, is the main part of the texts connected with the mother. They depict the daily relations between the adult daughter and her mother. The letters are much less concentrated texts than poetry pieces or an autobiography, with a lot of extra contexts, such as the realities of the daily life. However, due to them, the daily life acquires its volume and duration and provides a space for concentrated but fragmentary texts of poetry and autobiography. The inclusion of the mother into the autobiographical and poetical texts in this case was not easy and natural. It cost great efforts to the writer but was always pushed by some internal wish to be told. The article summarizes a collection of autobiographical texts encompassing a period of twenty years. We are allowed to observe how slowly and with great difficulty the narration grows about the experiences from childhood, what minimal and concentrated expressions are used. The process of the poetry of Degutytė can be seen as a constant self-opening to the tragic and painful experience. Her poetry becomes more and more explicit and open in tact with the telling about the relation to her mother. This correlation is not a coincidental but is a core fact that organizes the dynamic of the creation.